Religion as Moral Governance: Power, Exclusion, and Human Rights in Southeast Asia - Fonte, Allain; Huang, Shijie (Advances in Social Sciences Research Journal, 2026)
Religion plays a central role in shaping governance, legal authority, and moral legitimacy across Southeast Asia. While commonly framed as a source of ethical guidance and social cohesion, religion also functions as a system of moral governance that structures public policy, regulates social behavior, and delineates the boundaries of legitimate citizenship. Focusing on the Philippines, Indonesia, Malaysia, Thailand, Myanmar, Vietnam, and Brunei, this study examines religion not merely as belief or identity but as an institutionalized framework through which power, discipline, and exclusion are enacted. Drawing on comparative policy analysis, legal review, and synthesis of secondary qualitative evidence, the analysis demonstrates how religious doctrines are translated into law, enforcement practices, and administrative governance across Christian, Islamic, and Buddhist contexts. The findings show that religious moral frameworks are deeply embedded in state institutions governing family law, gender relations, sexuality, religious freedom, and citizenship. While these frameworks contribute to political legitimacy and social order, they simultaneously generate systematic exclusions affecting women, religious minorities, sexual minorities, indigenous communities, and stateless populations. Moral regulation—often justified as the preservation of cultural authenticity or religious values—renders access to rights and legal protection conditional on conformity to dominant norms, producing governance fragility in which human rights protections are uneven and vulnerable to political mobilization. This study concludes that sustainable human rights protection in Southeast Asia requires recognizing religion as a core component of governance and addressing moral governance as a structural determinant of rights outcomes in plural societies.